2021
DOI: 10.3389/fimmu.2021.576640
|View full text |Cite
|
Sign up to set email alerts
|

Early-Warning Immune Predictors for Invasive Pulmonary Aspergillosis in Severe Patients With Severe Fever With Thrombocytopenia Syndrome

Abstract: Aspergillus-related disease was confirmed to be associated with immune disorders in patients, severe patients with severe fever with thrombocytopenia syndrome (SFTS) infected by novel phlebovirus were confirmed to have severe immune damage including cellular immunosuppression and cytokine storms. Secondary invasive pulmonary aspergillosis (IPA) in severe SFTS patients can increase fatality rate. This study investigated early-warning predictive factors of secondary IPA in severe SFTS patients. Receiver operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 28 publications
9
19
2
Order By: Relevance
“…Use of antifungal drugs 25 ( Several studies have revealed that SFTSV infection is complicated by fungus-related co-infections (such as candidiasis and pulmonary aspergillosis). 7,9,12 This investigation revealed that A.…”
Section: Carbapenem Resistancementioning
confidence: 77%
See 1 more Smart Citation
“…Use of antifungal drugs 25 ( Several studies have revealed that SFTSV infection is complicated by fungus-related co-infections (such as candidiasis and pulmonary aspergillosis). 7,9,12 This investigation revealed that A.…”
Section: Carbapenem Resistancementioning
confidence: 77%
“…Various studies have reported an 8%–30% incidence of co‐infections among SFTS patients, however, it is unknown whether these infections are bacterial or fungal 4–6 . SFTSV infection has been documented to be worsened by fungal co‐infections like pulmonary aspergillosis and candidiasis 7–10 . Due to the severity of SFTS patients and the challenge of excluding an associated co‐infection based on clinical, radiological, or laboratory evidence, the majority of patients with SFTS were effectively treated with antibiotics following admission.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies previously demonstrated that cd3 + , cd4 + , and cd8 + T cells are diminished in patients with SFTS (94)(95)(96)(115)(116)(117)(118)(119) and in experimental animal models (103). Sun et al (94) revealed a significant decline in CD3 + and cd4 + expression in the peripheral blood of patients with SFTS, where the average leukocyte count was 2.86±1.56x10 9 /l.…”
Section: T-cell-mediated Immune Response To Sftsv T Lymphocytes Serve...mentioning
confidence: 99%
“…A major challenge is recognizing and treating critically ill patients and those who may die from SFTS. Even though there are already some studies describing the characteristics, predictors, or treatments of SFTS, most of them only discussed the association between fatal outcomes and various indicators, such as viral load, gender, comorbidities, age, and immune predictors that need special detection (He et al, 2020 ; Hu et al, 2021b ; Zhao et al, 2021 ). In addition, several studies tried to establish a special score model to forecast poor prognosis, which seemed difficult to count and limited in generalization (Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%